Applications on operations on weakly compact generalized topological spaces - Roy, B.; Noiri, T. (Carpathian Mathematical Publications, 2020)
In this paper, we have introduced the notion of operations on a generalized topological space $(X,μ)$ to investigate the notion of $γ_{_μ}$-compact subsets of a generalized topological space and to study some of its properties. It is also shown that, under some conditions, $γ_{_μ}$-compactness of a space is equivalent to some other weak forms of compactness. Characterizations of such sets are given. We have then introduced the concept of $γ_{_μ}$-$T_{_2}$ spaces to study some properties of $γ_{_μ}$-compact spaces. This operation enables us to unify different results due to S. Kasahara.